Critérios de Diagnóstico para Pesquisa das Desordens Temporomandibulares (RDC/TMD): avaliação de radiologistas sobre adequação - MACHADO, Luciana Pimenta e Silva (2011)
The aim of this study was to investigate the opinion of specialists in radiology, from different parts of the world, regarding to the proposed criteria for image acquisition and interpretation by Computed Tomography (CT), Cone Beam Computed Tomography (CBCT) and Resonance imaging (MRI) in diagnosing temporomandibular joint disorders (DATM) as part of Diagnostic Criteria for Research of Temporomandibular Disorders (RDC/TMD). Radiology specialists were invited by email to participate as volunteers in the study from three different eligible populations: researchers with publication DATM indexed on PubMed, ORADLIST members and individual contact. The link to access the questionnaire was mailed to volunteers interested in participating who matched the inclusion criteria. The sample was composed of specialists in radiology with experience in the interpretation of sectional images (CT, CBCT and/or MRI) of the temporomandibular joint (TMJ) who answered a questionnaire in English, which was developed and maintained online (LimeSurvey 1.87+). In a three months period, two recalls were sent and a period of 40 days after the last notification was given for responses submission. The questionnaire was divided into three parts with closed and open questions. Part I was related to issues of participant identification (gender, age, country of activity, area of activity, time and experience as a radiologist in the interpretation of sectional images of the TMJ and monthly time dedicated to the activity of interpreting sectional images of ATM). Part II contained questions related to the adequacy of the proposed criteria for the interpretation of sectional images of the ATM as part of the RDC/TMD. The criteria were presented into two columns' tables and the participants were asked whether that set of criteria was considered adequate or not for assessement and diagnosis of TMJ osseous and non-osseous tissues according to each imaging modality. If the respondent not considered criteria appropriate, he/she should indicate what type of suggestion: if insertion of new items, the modification or deletion of existing items. Part III had questions related to the need to include a minimal technical protocol for TMJ CT, CBCT and MRI acquisition as part of the RDC/TMD. If deemed necessary, the respondent should indicate which would be his/her suggestion protocol for acquisition of each imaging technique (CT, CBCT and MRI). Fifty-seven radiologists from different countries completed the questionnaire. The results indicate that 87 to 98% of radiologists considered the criteria adequate and that 81.6% of respondents considered necessary to include a minimal technical protocol for CT, CBCT and MRI acquisition as part of the RDC/TMD. Two to thirteen percent of respondents suggested insertion, modification and deletion of items in the proposed criteria. Ninety percent of respondents considered necessary to include a minimal technical protocol for CT/CBCT and 81.7% for MRI. We conclude that, according to the opinion of the worldwide community of specialists in radiology, the need for adjustments in the criteria for assessment of sectional images of the ATM is minimal, however, the need for the inclusion of a protocol to acquire minimal technical parameters of those images as part of protocol standardization of studies using the RDC/TMD is clear.